EFFECT OF CONSUMING GREEN BEAN (PHASEOLUS RADIATUS) JUICE ON MATERNAL BLOOD PROFILE DURING PREGNANCY - Stefani Anastasia S; Soehartono Soehartono; Ngadiyono Ngadiyono; Muchlis Muchlis; Dyah Dyah (Belitung Raya Foundation, Indonesia, 2017)
Background: Most of anemia in pregnancy is caused by iron deficiency. Thus, giving iron tablets is an effort to deal with anemia. A green bean (Phaseolus Radiatus) juice is considered helping the absorption of iron effectively. Objective: To analyze the effect of green bean (Phaseolus Radiatus) juice on changes in blood profile levels in pregnant women with anemia who received Fe tablet supplementation. Methods: This was a quasi-experimental study with pretest posttest with control group design conducted from November 2016 to January 2017 in the working area of the Community Health Center of Kedungmundu Semarang, Indonesia. Consecutive sampling was used in this study to select 40 samples based on the hypothesis formula of two independents. There were 20 samples assigned in each group. Data were analyzed using paired t-test and Independent t-test. Results: The results of this study showed that there were significant increases in hemoglobin, hematocrit, and erythrocytes (p = 0.000) after given green bean (Phaseolus Radiatus) juice. Conclusion: There was a significant effect of green bean (Phaseolus Radiatus) juice in increasing the levels of hemoglobin, hematocrit, and erythrocytes. It is expected that this green bean juice can be used as an alternative treatment to deal with anemia in pregnant women.